Serotonin Receptors in the Medulla Oblongata of the Human Fetus and Infant: The Analytic Approach of the International Safe Passage Study. Issue 11 (November 2016) - Haynes, Robin L.; Folkerth, Rebecca D.; Paterson, David S.; Broadbelt, Kevin G.; Dan Zaharie, S.; Hewlett, Richard H.; Dempers, Johan J.; Burger, Elsie; Wadee, Shabbir; Schubert, Pawel; Wright, Colleen; Sens, Mary Ann; et al.
Abstract : The Safe Passage Study is an international, prospective study of approximately 12 000 pregnancies to determine the effects of prenatal alcohol exposure (PAE) upon stillbirth and the sudden infant death syndrome (SIDS). A key objective of the study is to elucidate adverse effects of PAE upon binding to serotonin (5-HT) 1A receptors in brainstem homeostatic networks postulated to be abnormal in unexplained stillbirth and/or SIDS. We undertook a feasibility assessment of 5-HT1A receptor binding using autoradiography in the medulla oblongata (6 nuclei in 27 cases). 5-HT1A binding was compared to a reference dataset from the San Diego medical examiner's system. There was no adverse effect of postmortem interval ⩽100 h. The distribution and quantitated values of 5-HT1A binding in Safe Passage Study cases were essentially identical to those in the reference dataset, and virtually identical between stillbirths and live born fetal cases in grossly non-macerated tissues. The pattern of binding was present at mid-gestation with dramatic changes in binding levels in the medullary 5-HT nuclei over the second half of gestation; there was a plateau at lower levels in the neonatal period and into infancy. This study demonstrates feasibility of 5-HT1A binding analysis in the medulla in the Safe Passage Study.